Shared cis-regulatory architecture identified across defense response genes is associated with broad-spectrum quantitative resistance in rice - Tonnessen, Bradley W.; Bossa-Castro, Ana M.; Mauleon, Ramil; Alexandrov, Nickolai; Leach, Jan E. (Springer, 2019)
Plant disease resistance that is durable and effective against diverse pathogens (broad-spectrum) is essential to stabilize crop production. Such resistance is frequently controlled by Quantitative Trait Loci (QTL), and often involves differential regulation of Defense Response (DR) genes. In this study, we sought to understand how expression of DR genes is orchestrated, with the long-term goal of enabling genome-wide breeding for more effective and durable resistance. We identified short sequence motifs in rice promoters that are shared across Broad-Spectrum DR (BS-DR) genes co-expressed after challenge with three major rice pathogens (Magnaporthe oryzae,Rhizoctonia solani, andXanthomonas oryzaepv.oryzae) and several chemical elicitors. Specific groupings of these BS-DR-associated motifs, calledcis-Regulatory Modules (CRMs), are enriched in DR gene promoters, and the CRMs includecis-elements known to be involved in disease resistance. Polymorphisms in CRMs occur in promoters of genes in resistant relative to susceptible BS-DR haplotypes providing evidence that these CRMs have a predictive role in the contribution of other BS-DR genes to resistance. Therefore, we predict that a CRM signature within BS-DR gene promoters can be used as a marker for future breeding practices to enrich for the most responsive and effective BS-DR genes across the genome.